PERBEDAAN KELARUTAN KALSIUM PADA GIGI DESIDUI DAN GIGI PERMANEN DALAM PERENDAMAN MINUMAN BERKARBONASI RASA BUAH - Octa Nana Erviana; Diyah Fatmasari; Benni Benyamin (Faculty of Dentistry, Universitas Islam Sultan Agung, 2015)
Introduction: SThe carbonated beverage is the main factor causing tooth erosion due to acidic and mass consumed, especially by children and adolescents.Purpose: This study was conducted to determine the differences between solubility of calcium in deciduous teeth and permanent teeth in the soaking fruit-flavored carbonated beverage.Methods: The research was a quasi experimental research with the formulated research post test only design. The sample used was 24 teeth, which consists of 12 deciduous incisors central teeth of the maxillary and 12 incisor central permanent teeth of the maxillary. The samples were divided into 6 groups and treated by soaking in the carbonated soft drinks for 30, 45, and 60 minutes. The data analysis used in this reasearch was a Two Way ANOVA test with probability p<0.05. Furthermore, the data were analyzed by the Tukey HSD test to determine the differences in each group.Results: Based on Two Way ANOVA test that was conduct, it was obtained significance value of 0.000 (p <0.05), so it can be concluded that there are significant differences between groups. From Tukey HSD test it was obtained a significance value of p<0.05 in all groups. It means that there are significant differences between each group, except in the immersion group of deciduous teeth 30 minutes with the permanent teeth 45 minutes that obtained 0,929 significance (p>0.05). It means that there was no significant differences between the two treatment groups. The result of the data analysis reveals that there was a difference in the solubility of calcium in deciduous teeth and permanent teeth. The solubility of calcium in deciduous teeth was larger than the permanent teeth at all time duration, because of the deciduous teeth had thinner and permeable enamel than permanent teeth.